Pemikiran Abdurrahman Wahid tentang Islam dan Humanisme - Lestari, Puput Dwi (Matan: Journal of Islam and Muslim Society, 2020)
In the Islamic world itself, the idea of humanism has been started since the beginning of Islamic history, namely when there was a debate between various schools of kalam about human destiny. The question that is often asked is whether humans have the freedom to determine their own destiny or humans have no free will at all, but their fate is determined by God. Abdurahman Wahid (Gus Dur) is one of the prominent Islamic figures who carries the idea of humanism. The enormous contribution of the ideas of Gus Dur's humanism, according to the author, is very important to study, this is because the ideas of Gus Dur's humanism are needed to understand Islam in relation to the problems of humanity and civilization. This is where the ideas of Gus Dur's humanism are believed to be able to answer the problems of the Indonesian people in relation to humanitarian issues, such as backwardness, poverty and ignorance. In order to synthesize between Islamic insights and Indonesian-Indonesian contexts, the writer tries to present a new breakthrough by examining Gus Dur's humanism ideas more. By using the Library Research method (literature review) the author tries to explain the idea of Gus Dur's humanism. This idea was obtained by the writer by reading and understanding various books by Gus Dur as primary data and several scientific journals as supporting data. The results of this paper stated that in Gus Dur's view, aspects of humanism were revealed in several important terms, firstly guaranteeing freedom of religion, secondly guaranteeing the protection of basic human rights, thirdly democratic culture, fourthly protecting minorities.